2002
DOI: 10.1038/sj.ejcn.1601419
|View full text |Cite
|
Sign up to set email alerts
|

Daidzein and genistein content of cereals

Abstract: Objective: To analyse 75 cereals and three soy flours commonly eaten in Europe for the phytoestrogens daidzein and genistein. Design: The phytoestrogens daidzein and genistein were extracted from dried foods, and the two isoflavones quantified after hydrolytic removal of any conjugated carbohydrate. Completeness of extraction and any procedural losses of the isoflavones were accounted for using synthetic daidzin (7-O-glucosyl-4 0 -hydroxyisoflavone) and genistin (7-O-glucosyl-4 0 5-dihydroxyisoflavone) as inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
96
0
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(101 citation statements)
references
References 20 publications
1
96
0
4
Order By: Relevance
“…Data from Italy and Ireland have estimated that over 90% of total isoflavone intake comes from bread (Van Erp-Baart et al, 2003). UK data on isoflavone content of bread (Liggins et al, 2002) is available but there are as yet no detailed data on milk, dairy products, meat and fish products, which have been shown to contain isoflavones (King et al, 1998;Antignac et al, 2003;. While the database created for this investigation does contain values for some meat products, it was felt that there was insufficient information available to estimate isoflavone content of fish products.…”
Section: Discussionmentioning
confidence: 99%
“…Data from Italy and Ireland have estimated that over 90% of total isoflavone intake comes from bread (Van Erp-Baart et al, 2003). UK data on isoflavone content of bread (Liggins et al, 2002) is available but there are as yet no detailed data on milk, dairy products, meat and fish products, which have been shown to contain isoflavones (King et al, 1998;Antignac et al, 2003;. While the database created for this investigation does contain values for some meat products, it was felt that there was insufficient information available to estimate isoflavone content of fish products.…”
Section: Discussionmentioning
confidence: 99%
“…The direct measurement of phyto-oestrogen concentrations in the circulation makes it possible to capture phyto-oestrogen exposure from all sources, including those that may be inadequately represented in food composition databases. For example, although the most abundant sources of isoflavones in the diet are soy foods, such as tofu and soymilk, the intake of which is low but variable across the European countries in EPIC (Keinan-Boker et al, 2002), soy additives are now also found in an increasing range of processed foods (Liggins et al, 2002). Isoflavones are also present in certain other vegetables, fruits and nuts (Liggins et al, 2000a, b), although in much lower concentrations than in soy foods.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few nonsoy plants contain isoflavones (e.g., legumes, grapefruit and raisins); but, at lower concentration, isoflavones do not importantly contribute to phytoestrogen intake in Western diets. 11,12 Plant lignans are widely present in whole grain, berries, vegetables, fruits, flaxseeds and other types of seeds and are the main source of phytoestrogens in Western populations. 13 Plant lignans (lariciresinol, pinoresinol, secoisolariciresinol and matairesinol) are metabolized into mammalian lignans (enterolignans: enterolactone, enterodiol) in the human gut.…”
mentioning
confidence: 99%